Indonesian Cultural Identity In The Message Of Public Service Announcements From Film Sensor Institutions 2014 - Agus Hermanto; Sa’diyah El Adawiyah (INJECT (Interdisciplinary Journal of Communication), 2020)
This study aims to determine the Indonesian cultural identity, visual forms of identity, and the visual meaning of Indonesian cultural identity in the message of Public service announcements at television from Film Sensor Institutions in 2014. This study is a qualitative research of constructivism paradigm with semiotics analysts. The findings of this study show the diversity of cultural identity has the potential that can be developed to have more value and added value, both from the economic side as well as from the social and cultural side. That traditional culture can be side by side and synergize with the advancement of time and the advancement of existing technology, can advance Indonesian traditional culture and Indonesian traditional culture can help technological advancement. It also shows that the diversity of Indonesian culture can be one of the drivers in the advancement of the film industry in Indonesia and film becomes a promotional tool for Indonesian cultural diversity.